"Post Modern Medicine" would be "calculable and energy-based medicine": A hypothesis paper. Issue 2 (December 2015) - Yousefi, Hila; Rezaei, Nima
Graphical abstract: Highlights: We model a new approach towards the human body system named "Post Modern Medicine". Therapeutic energy would be exposed toward the specific atom or subatomic particles. This approach needs less cost and time, with no risk of chemical interactions. Science is an endless search for the truth and there is no finality in the science. We portray the future of medical science. Abstract: The approach of current modern medicine towards human body system is solely molecular and cellular. Despite the great efforts, current medicine has not been successful enough, and spectrum of disorders has remained untreated. It emphasizes on the essential need for more careful approach to the body system. Prior to the molecules and cells human body system has been composed of countless of atomic and subatomic particles, considering laws of quantum physics and the principles of chemistry the energy levels of energy photons of these particles play the most crucial role in designing human body characteristics and conformations.In this hypothesis paper, we outline the novel approach towards human body system and concluded that exposing a form of energy to the energy photons of the subatomic particles in one of the molecules of oxygen bound to phosphor in phosphate group would be beneficial therapeutic method regarding all types of cancers, refuting concerns of variety of gene mutations and signaling cascades engaged with engendering and progression of various types of cancers.